Analysis of the determinants of spatial-temporal dynamics in secondary cities in central Africa: Case study of Foumbot in western Cameroon - Honoré, Ayiwouondinine Kouotou Jean; Danvide, Taméon Benoît; Naringue, François Teadoum; Ghislain, Allarane Ndonaye; Aholou, Coffi Cyprien (Edelweiss Applied Science and Technology, 2025)
Foumbot, an important agricultural hub in Central Africa, faces many challenges linked to its rapid urban growth. This study aims to analyze the determinants of Foumbot’s spatiotemporal dynamics between 1990 and 2020. The methodology used focuses on the analysis of Landsat satellite images and socioeconomic data, as well as documentary analysis, direct observation, and interviews with key informants. The results reveal that the built-up area increased from 138.19 hectares (ha) in 1990 to 671.31 ha in 2020, an almost fourfold increase. In contrast, water bodies, bare land, and vegetation have decreased significantly, from 430.58 ha, 342.07 ha, and 184.81 ha in 1990 to 116.86 ha, 143.78 ha, and 163.69 ha in 2020, respectively. These spatial and temporal changes, which underline the influence of urbanization on the natural environment, were mainly driven by factors such as population growth, the crisis in the coffee economy and the boom in food crops during the 1990s, and the city’s administrative and commercial functions. This spatial dynamic increases pressure on natural resources. Consequently, integrating environmental issues into sustainable urban planning policies is crucial to reconciling urbanization with environmental preservation and promoting a sustainable transition in land use.